Program integration in multi-project change programs: agency in integration practice. Issue 4 (May 2018) - Vuorinen, Lauri; Martinsuo, Miia
Abstract: Multi-project change programs pursue challenging goals and may suffer from uncertainty and conflicting interests. To achieve their goals, such programs need integration both with the parent organization and between projects. There is a need for knowledge on how program actors implement integration. This study pursues new knowledge on program actors' agency in program integration in the context of multi-project change programs. Two case programs in different contexts were explored, to map their integration mechanisms and program actors' integration activities during the program lifecycle. The results reveal five integration tasks, the program-specific use of integration mechanisms, differences in the integration approach between the two programs, and the parent organization's input at the program front end in defining the program's requisite autonomy. The organization's maturity in project-based organizing, the program and project managers' competence, and the autonomy enabled at the program front end are shown to define the programs' integration practice. Highlights: Program integration leads toward change goals through five integration tasks. Expertise in project organizing and project autonomy explain integration practice. Choices in program front end define actors' agency in program integration. Program managers act as internal support persons and visionary idea generators.